6‐2: Invited Paper: High‐ppi Fast‐Switch Display Development for Oculus Quest 2 VR Headsets. Issue 1 (28th June 2022) - Kim, Cheonhong; Klement, Alex; Park, Eric; Han, Jason; Rao, Linghui; Zhuang, Jim
Abstract : Recently, Meta rolled out Oculus Quest 2 all‐in‐one VR systems which have brought more virtual reality entertainment and experiences for users to discover. A 5.46″ 773 PPI (pixel per inch), 1920 RGB × 3664, fast‐switch LCD with low‐persistence backlight is used to get visual fidelity of around 21 PPD (pixel per degree) without any blur or ghost artifact. In this paper, we will present the overview of Quest 2 display architecture, performances and some of the design challenges which we have addressed.